Natural course of photic maculopathy secondary to uncomplicated cataract surgery. (17th January 2013) - Querques, Lea; Querques, Giuseppe; Cascavilla, Maria Lucia; Triolo, Giacinto; Lattanzio, Rosangela; Introini, Ugo; Bandello, Francesco
<x xml:space="preserve">Abstract</x> We report on a 36‐year‐old man who developed photic maculopathy in the left eye shortly after uncomplicated cataract surgery. The visual acuity (VA) of the left eye was 6/39 and spectral domain optical coherence tomography (SD‐OCT), performed one week after surgery, revealed a hyporeflective space in the outer retina (a 'partial‐thickness hole') at the fovea. Microperimetry showed a relative central scotoma and multifocal electroretinogram (ERG) showed reduced responses within the central 10°. Two months later, VA in the felt eye improved to 6/6 and SD‐OCT showed an almost complete resolution of the 'partial‐thickness hole'. Microperimetry showed the resolution of the relative scotoma at the fovea and multifocal ERG showed improved responses within the central 10°. SD‐OCT, microperimetry and multifocal ERG are useful tools in the diagnosis and follow‐up of photic maculopathy after uncomplicated cataract surgery. Its natural history may be characterised by resolution of both morphological and functional changes shortly after surgery.